2013
DOI: 10.1021/np4005882
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Phytotoxin Alternariol 9-Methyl Ether and Some of Its Synthetic Analogues Inhibit the Photosynthetic Electron Transport Chain

Abstract: Alternariol and monomethylalternariol are natural phytotoxins produced by some fungal strains, such as Nimbya and Alternaria. These substances confer virulence to phytopathogens, yet no information is available concerning their mode of action. Here we show that in the micromolar range alternariol 9-methyl ether is able to inhibit the electron transport chain (IC50 = 29.1 ± 6.5 μM) in isolated spinach chloroplasts. Since its effectiveness is limited by poor solubility in water, several alternariol analogues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Interestingly, AME has been reported to suppress cyanobacterial growth by inhibiting the photosynthetic electron transport chain (79). In this study, we showed that the virulence of ⌬SnPKS19 against wheat leaves in vitro is comparable to that of the wild type; thus, AOH is unlikely to play a role in pathogenicity.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, AME has been reported to suppress cyanobacterial growth by inhibiting the photosynthetic electron transport chain (79). In this study, we showed that the virulence of ⌬SnPKS19 against wheat leaves in vitro is comparable to that of the wild type; thus, AOH is unlikely to play a role in pathogenicity.…”
Section: Discussionmentioning
confidence: 56%
“…Fusicoccin (Figure 5 ) [ Fusicoccum ( Phomopsis ) amygdali ] irreversibly activated the plant plasma membrane H + -ATPase (Paiardini et al, 2014 ). Alternariol (Figure 2 ) and monomethyl alternariol are natural phytotoxins, produced by Nimbya and Alternaria , inhibited the electron transport chain (Demuner et al, 2013 ). Cerulenin (Figure 5 ) ( Cephalosporium cerulens ) inhibited de novo fatty acid synthesis in plastids (Laskay et al, 1985 ).…”
Section: Phytopathogenic Fungimentioning
confidence: 99%
“…AOH facilitated the infection and colonization of A. alternata on tomato, citrus and apple by the addition of AOH to pksI -deletion mutant, but the chemical alone exhibited no phytotoxin in wheat leaves and seed germination [10,11]. Correspondingly, AME enabled the inhibition of photosynthetic electron transport in extracted spinach chloroplasts [12].…”
Section: Introductionmentioning
confidence: 99%